Potencialidades de uma sequência didática com enfoque CTSA no desenvolvimento da educação ambiental no ensino fundamental - Oliveira, Samuel Martins Lima de (2023)
The National Common Curricular Base (BNCC) advocates the importance of Environmental Education (EE) in Basic Education, recommending that it be approached not as a specific curricular component, but as a transversal theme, aiming, therefore, to interconnect the different objects of knowledge of curricular components to environmental impacts and ways of preserving natural resources for sustainability. However, for the insertion of EA that allows a broad approach in all its senses, covering the social, economic, political and cultural spheres, a methodology is necessary that contemplates these aspects, different from what is practiced, with a focus only focused on ecology. In this way, the production of teaching materials that deal with EE, in an integral way, can serve as support for the inclusion of environmental issues in the curricular components that make up the school curriculum. In turn, following today's society, the insertion of Information and Communication Technologies (ICTs), as allies, can enhance the search for this EE focused on citizenship, with the use of educational applications. Given this, the question that guides the research is: What are the potential of a didactic sequence with a Science-Technology-Society-Environment (CTSA) focus for the development of EA in Elementary Education? In order to answer this question, the general objective is to develop, apply and evaluate a didactic sequence in light of the CTSA approach, which contemplates the use of ICTs in a perspective that strengthens the relationship between EE and the objects of scientific knowledge and the local needs, encouraging more sustainable practices in caring for the environment. The didactic intervention was developed in five stages, requiring three meetings, totaling 15 hours, with 16 students from the 6th year of Elementary School at the Girassol school, in Valença, State of Bahia. In this study, a smartphone application entitled PROUSA (Sustainable Water Use Program) was developed, which is included in the didactic sequence. The research assumes a qualitative approach, involving the production of data through instruments: logbook of the research teacher, questionnaire and materials produced by the students themselves. The results of the study indicate that the use of the didactic sequence in CTSA was well accepted by students and provided a methodological alternative for teaching EA in a school environment. The students showed themselves to be participative, making it possible to discuss and debate aspects of EE that are not only linked to the preservation of the natural environment, but to all the actors that are part of EE for sustainability and citizenship, such as the social, economic, political and cultural bias . The educational product will be available freely and freely on the program website, on the educational products portal of the Postgraduate Program in Science and Mathematics Teaching (PPGECM) and on the EduCapes portal at the link http://educapes.capes.gov .br/handle/capes/739498.